Promoting peace journalism during conflict situations: challenges and prospects - Masum, Ahmad; Nafees, Seeni Mohamed; Ahmad, Muhamad Hassan (IIUM Press, 2022)
The traditional approach of the media to conflict has been shaped by power, politics, and profit. However, in recent decades, the debate over “peace journalism” as a conflict resolution strategy has gained traction, with several scholars arguing in favour of the concept. Most wars would have gone unnoticed if there were no journalists to report on them and no news organisations to send reporters to conflict zones. At the same time, the media frequently prioritises conflict and war over playing a positive role in efforts to achieve peace. As a result, peace journalism is viewed as an alternative model to traditional methods of war reporting. Many questions about the effectiveness of peace journalism and its application to other forms of media, however, remain unanswered. Despite its noble goal, it ignores the media’s numerous nuances and tends to highlight the exceptional, spectacular, and negative aspects of war coverage. This paper attempts to find answers to these questions. The paper relies on available data and thematic discourse on peace journalism during conflict situations. The paper contends that the traditional media’s approach to conflict situations is undergoing a paradigm shift. Additionally, the paper concludes that while peace journalism has traditionally been associated with conflict resolution and advocacy, it is now more widely accepted as an attitude that frames a news story. Finally, the paper recommends that the media should play a role in conflict situations. The nature of that role—as a perpetrator of a conflict or an agent of peace—is heavily influenced by the media’s framing and agenda-setting. In addition, the paper also recommends that to have any influence on how news is produced and scrutinised, it is necessary to address the structural constraints of news production. Peace journalism, and especially its practical implications, must be discussed in the context of journalism studies, where it resonates with ongoing efforts to promote excellence in journalism.